Data-driven fuel consumption estimation: A multivariate adaptive regression spline approach. (October 2017) - Chen, Yuche; Zhu, Lei; Gonder, Jeffrey; Young, Stanley; Walkowicz, Kevin
Highlights: We developed a mesoscopic fuel consumption estimation model. Data-driven multivariate adaptive regression spline approach was used to establish fuel estimation relationship. The model cluster road links by free flow speed and fit regression curves according to cluster characteristics. Abstract: Providing guidance and information to drivers to help them make fuel-efficient route choices remains an important and effective strategy in the near term to reduce fuel consumption from the transportation sector. One key component in implementing this strategy is a fuel-consumption estimation model. In this paper, we developed a mesoscopic fuel consumption estimation model that can be implemented into an eco-routing system. Our proposed model presents a framework that utilizes large-scale, real-world driving data, clusters road links by free-flow speed and fits one statistical model for each of cluster. This model includes predicting variables that were rarely or never considered before, such as free-flow speed and number of lanes. We applied the model to a real-world driving data set based on a global positioning system travel survey in the Philadelphia-Camden-Trenton metropolitan area. Results from the statistical analyses indicate that the independent variables we chose influence the fuel consumption rates of vehicles. But the magnitude and direction of the influences are dependent on the type of road links, specifically free-flow speeds of links. A statistical diagnostic is conducted to ensure the validity of the models and results. Although the real-world driving data we used to develop statistical relationships are specific to one region, the framework we developed can be easily adjusted and used to explore the fuel consumption relationship in other regions.